A novel conceptual model and heuristic tool to strengthen understanding and capacities for health inequalities research - Lucinda Cash-Gibson; Matthew Harris; Germán Guerra; Joan Benach (BMC, 2020)
Abstract Background Despite increasing evidence on health inequalities over the past decades, further efforts to strengthen capacities to produce research on this topic are still urgently needed to inform effective interventions aiming to address these inequalities. To strengthen these research capacities, an initial comprehensive understanding of the health inequalities research production process is vital. However, most existing research and models are focused on understanding the relationship between health inequalities research and policy, with less focus on the health inequalities research production process itself. Existing conceptual frameworks provide valuable, yet limited, advancements on this topic; for example, they lack the capacity to comprehensively explain the health (and more specifically the health inequalities) research production process at the local level, including the potential pathways, components and determinants as well as the dynamics that might be involved. This therefore reduces their ability to be empirically tested and to provide practical guidance on how to strengthen the health inequalities research process and research capacities in different settings. Several scholars have also highlighted the need for further understanding and guidance in this area to inform effective action. Methods Through a critical review, we developed a novel conceptual model that integrates the social determinants of health and political economy perspectives to provide a comprehensive understanding of how health inequalities research and the related research capacities are likely to be produced (or inhibited) at local level. Results Our model represents a global hypothesis on the fundamental processes involved, and can serve as a heuristic tool to guide local level assessments of the determinants, dynamics and relations that might be relevant to better understand the health inequalities research production process and the related research capacities. Conclusions This type of knowledge can assist researchers and decision-makers to identify any information gaps or barriers to be addressed, and establish new entry points to effectively strengthen these research capacities. This can lead to the production of a stronger evidence base, both locally and globally, which can be used to inform strategic efforts aimed at achieving health equity.